Development of Explain Everything Learning Media Through an Active Learning Approach to Improve Understanding of Tajwīd Subject - Ulifah Azwarani Rochmah; Sutiah Sutiah (DAYAH: Journal of Islamic Education, 2023)
After the COVID-19 pandemic, educational institutions in Indonesia, including non-formal educational institutions such as tutoring, adapted to online learning. However, new issues arise when students are unable to comprehend the material presented by the teacher or tutor on a variety of subjects, including tajwid. The Explain Everything learning platform is a digital whiteboard with a variety of intriguing features. This medium is most effective when combined with an approach to active learning. The study was conducted using the Research and Development (R&D) method of study with the ADDIE development model. Based on the evaluation and validation of subject matter experts, media specialists, and instructors, the Explain Everything learning media was deemed feasible with an average of 84.3%. According to the learning outcomes, the Explain Everything-based learning media for class five at Mardin Private Elementary School was successful in enhancing students' understanding of tajwid material.